Effectiveness of ensitrelvir for cough caused by COVID-19 Omicron variant in patients with asthma - Naoyuki Miyashita; Nobuyuki Horita; Yasushi Nakamori; Makoto Ogata; Naoki Fukuda; Akihisa Yamura; Tomoki Ito (Microbiology Spectrum)
ABSTRACT In the post-acute coronavirus disease 2019 (COVID-19) period, patients with asthma had a significantly higher risk of cough than patients without a history of asthma. In particular, cases with persistent cough were increased during the Omicron variant epidemic. In this study, we evaluated the efficacy of ensitrelvir for the treatment of cough associated with COVID-19 Omicron variants in patients with asthma. This follows the Strengthening the Reporting of Observational Studies in Epidemiology statement. A total of 223 patients were registered in this study: 121 patients chose ensitrelvir, and 102 patients chose symptomatic treatment. Cough severity, frequency, and cough-specific quality of life were evaluated using the Japanese version of the Leicester Cough Questionnaire (J-LCQ). J-LCQ documented at baseline on days 4, 7, and 14 for all patients showed a steady improvement over time in both groups. In the mixed model for repeated measures model, which accounts for repeated measurements, the change in J-LCQ score from baseline was 2.1 points higher in the ensitrelvir group (P <0.001). Additionally, patients who were using triple inhaled therapy at baseline showed a 2.3-point higher change in J-LCQ score from baseline (P <0.001). Multiple regression analysis was performed at days 4, 7, and 14, with the change in J-LCQ score from baseline as the dependent variable. Ensitrelvir was associated with scores that were 3.1 points higher on day 4, 3.5 points higher on day 7, and 2.0 points higher on day 14 compared with symptomatic treatment (P <0.001 for all). In conclusion, our results demonstrated that early administration of ensitrelvir may be effective as a treatment for cough due to the COVID-19 Omicron variant.IMPORTANCEWe evaluated the efficacy of ensitrelvir for the treatment of cough due to coronavirus disease 2019 (COVID-19) Omicron variant in patients with asthma. A total of 223 patients were registered in this study: 121 patients chose ensitrelvir, and 102 patients chose symptomatic treatment. Cough severity, frequency, and cough-specific quality of life were evaluated using the Japanese version of the Leicester Cough Questionnaire (J-LCQ). Multiple regression analysis was performed at days 4, 7, and 14, with the change in J-LCQ score from baseline as the dependent variable. Ensitrelvir was associated with scores that were 3.1 points higher on day 4, 3.5 points higher on day 7, and 2.0 points higher on day 14 compared with symptomatic treatment (P <0.001 for all). Our results demonstrated that early administration of ensitrelvir may be effective as a treatment for cough due to the COVID-19 Omicron variant.